INVESTIGATION OF THE EFFECTS OF TRIBULUS TERRESTRIS ON THE INFLAMMATION IN THE LIVER INJURY INDUCED BY CARBON TETRACHLORIDE - Cambay, Zafer; Alayunt, Naci Omer (Parlar Scientific Publications (P S P), 2019)
In this study, it has been aimed to investigate the effects of the plant Tribulus terrestris whether it is effective as a liver protective agent with an antiinflammatory effect against carbon tetrachloride (CCI4), which is hepatotoxic when used chronically, and it has been aimed to examine the degree of its effectiveness when such an effect has been observed. In the study, 35 Wistar-Albino male rats aged 8-12 weeks were used. The rats were assigned to five groups of seven rats each. The rats were fed with a standard diet in all groups. Excluding the control group, all rats in the other groups received CCl4 at a dose of 0.8 ml/kg administered intraperitoneally for 14 days. CCl4 was administered to the rats in the groups 3, 4, and 5 and this period was followed by the administration of Tribulus terrestris plant extract for a period of 8 weeks. The serum levels of NO, TNF-alpha, IL-6, and IL-1 beta were tested in the rats. It was observed that all study parameters increased significantly in the CCL4 group compared to the control group (p<0.01). Compared to the CCl4 group, the study parameters decreased in all treatment groups (p<0.01) and the extent of decrease was the highest in the group 5, where a high dose of Tribulus terrestris extract was administered. While the levels of NO, TNF-alpha, IL-6, and IL-1 beta decreased significantly in the treatment groups compared to the CCl4 group, the reduction in the NO and IL-6 groups approached to the levels observed in the control group. This study has demonstrated that the Tribulus terrestris plant has a liver protective effect against CCl4 which is known with its toxic effects and which induces inflammation in the rat liver. More effective results were observed especially with the higher doses of this plant's extract. We are of the opinion that the extract of Tribulus terrestris can be beneficial in human beings when used either for preventive purposes or for its anti-inflammatory effects and it can be considered as a supplement in the clinical treatment of liver diseases, becoming one of the agents in adjuvant treatments.
Keywords: Carbon tetrachloride; Tribulus terrestris; Inflammation; interleukin